Development of the Socioecopreneur for Children (MSC) Module as an Effort to Support Sustainable Main Tourism Destination Programs at Public Elementary School( SDN) 04 Kampung Bajo Torosiaje - Jenli Abbas, Moh.; Maulidyawanti Moonti, Gusfin; Samad, Pratiwi; Suryani Munir, Fairus (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Bajo Village of Torosiaje is part of the selected DSP based on its tourism potential to boost the economy through the tourism industry. The main issue that arises is waste management. Poor waste management has led to the accumulation of waste along several roads leading to the tourist sites in Kampung Bajo Torosiajegies. Purpose. The development of this modul aim to foster children’s growth of the tourism industry in Bajo Torosiaje including in the awareness of social, envoronmental and economic sustainability as well as mproving human resource quality, setting it apart from other programs. Method. The methodology employs a Research and Development (R&D) approach based on the 4D model by Thiagarajan, focusing on a Socioecopreneurship Business Plan. This plan includes business planning materials and socioecopreneurship activities, incorporating socioecopreneur character values tailored for elementary school students. Results. The ecopreneurship-based learning approach significantly boosted students' entrepreneurial interest and environmental literacy. Interest scores increased from 69 to 72, while the percentage of students with low interest dropped from 27% to 3%. Additionally, 80% of students expressed satisfaction with the approach, indicating enthusiasm for utilizing local resources. Conclusion. These findings reflect a stronger understanding of sustainability among students and greater readiness to become environmentally conscious young ecopreneurs.